Wave Analysis Of Breakwater Building Structure In North Kalimantan - Rahman, Sabaruddin; Pairunan, Teguh (Maritime Park: Journal of Maritime Technology and Society, 2022)
Natural factors in the form of large sea waves occur on the beach located in Tanjung Aru Village, East Sebatik District, Nunukan, North Kalimantan, causing the beach This area is experiencing a decline in the coastline or what is commonly referred to as coastal erosion. In connection with these conditions, there has been a breakwater detached as an effort to solve this problem to protect coastal areas that are experiencing erosion. But before that, it is necessary to conduct a wave analysis of the design of the breakwater detached to be built. Based on the calculation analysis that has been done, the significant wave height (Hs) is 4,361 meters and the significant wave period (Ts) is 11.173 seconds. The pressure wave force (P) is 27.001 tons and the moment (Mp) is 92.612 tonmeters. Wave height measurements need to be carried out every month throughout the year in order to obtain a more representative picture of wave height. In addition, planning for the construction of breakwater needs to be considered again, especially on the dimensions of the breakwater structure. Moreover, the condition of the sea waves is fully developed.